THE STUDY OF SUBTITLING STRATEGY IN 'ALL TOO WELL' SONG TRANSLATION - Ivonda Seran; Agus Subiyanto (Wiralodra English Journal, 2023)
This study analyzes and discusses the subtitling strategies of the song translation "All Too Well (10-minute version)" from English to Indonesian. The data are taken from Taylor Swift's official lyrics video and the Indolirik channel on YouTube. The study is descriptive qualitative, and content analysis is applied in studying the data and gaining results. The study uses Gottlieb's (1992) 10 subtitling strategies focusing on audiovisual translation. The results show that there are four strategies found in the translated song lyrics: paraphrase (36%), transfer (32%), condensation (22%), and expansion (10%). The paraphrase strategy is probably used because most of the lyrics contain figurative expressions; therefore, the translator managed to convey their basic meaning rather than translating them with equivalent expressions. Meanwhile, the expansion strategy is the least used in translation because the translator might consider that most lyrics do not need more information in the target text. The song lyrics are generally well-conveyed; hence, the whole lyrics' meaning is interconnected and understandable.